IMPLEMENTASI INOVASI KURIKULUM PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5): TINJAUAN TERHADAP EFEKTIVITAS DAN DAMPAKNYA DALAM PEMBENTUKAN KARAKTER - Khalifatun, Salsa; Nuraida, Nuraida; Agustin, Salsabila; Agafe Pakpahan, Veriana Erfina; Kamandana Robbi, Muhammad Ij'alni; Setiyadi, Bradley (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study deals with the implementation of innovation curriculum of the Pancasila (P5) Student Profile Enhancement project as well as an overview of its effectiveness and impact in student character formation. The method used is the Literature Systematic Review (SLR) which involves the analysis of ten related articles. Many of the previous researchers have discussed the Merdeka Curriculum, however, still few are discussing P5 specifically especially how effective and impact on student character formation. This study aims to analyze the implementation of the independent P5 curriculum in Indonesia. Although P5 project-based activities are still new to the independent curriculum, the results show good effectiveness. The enthusiasm of students for the many projects created by teachers or even the government is huge. The findings of this research provide further understanding of the importance of innovation in the curriculum to shape the character of students in accordance with Pancasila's values. The results of the library survey analysis of the interactive, collaborative project-based approach used in the P5 successfully improved the understanding, appreciation, and practice of implementation of Pancasila values among students. However, there are challenges such as the availability of resources and the need for regular monitoring and evaluation to be taken into account in an effort to maintain the quality of implementation of the P5 curriculum.